A life cycle assessment of CCU process to produce a nanocomposite from ethanol plant CO2 emission - Ana Paula Rodrigues de Souza; Silvio Vaz, Jr.; Érica Gonçalves Gravina; Bruno Eduardo Lobo Baeta (Heliyon)
The use of rubber septa for controlled release of semiochemicals has raised important discussions about their efficiency and environmental impact since they are composed of fossil raw material. The life cycle assessment (LCA) of the synthesis of a nanocomposite type calcium nanocarbonate/Kraft lignin (NC-CN-KL) obtained from CO2 capture aimed to quantify the environmental loads involved in the production process. The synthesis evaluated by the LCA was performed on a laboratory scale, since it is a synthetic route classified as technological readiness level 4 (TRL-4) and is in the study and development stage. The LCA was performed according to the principles of the ISO 14044/2006 series of standards, from 101.854 g of nanocomposite as a functional unit. The limitations of the study arose from its synthesis scale, absence of LCA data on the rubber septa and other nanocomposites. The results obtained in the LCA identified electricity and other energy generation processes as the largest contributors to environmental loads for all environmental impact categories studied and suggest that research should focus on these inputs when choosing the sources used in energy nanocomposite formulation processes. LCAs for this synthesis to obtain NC-CN-KL should be carried out on a pilot scale, and it is expected that this work will contribute to the formulation of the material and decision-making, especially regarding the choice of the energy matrix.